Digital Well-Being As A Strategic Asset: A Systematic Review Of Paradoxical Effects Of Connectivity On Eudemonic Consumer Outcomes - Zahrotul Ulya (Journal of Marketing Breakthroughs, 2025)
Objective: This study aims to conduct a systematic review of the literature on digital well-being, focusing on the paradigm shift from merely reducing screen time to achieving profound eudaimonic consumer outcomes. This study investigates how the paradoxical effects of digital connectivity can be managed and transformed into a strategic asset for organizations in building brand equity and long-term loyalty. Research Design & Methods: Using a Systematic Literature Review (SLR) protocol guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, an analysis was conducted on 84 scientific publications from Q1-ranked journals from 2018 to 2026. The selection process included identifying central themes, conducting qualitative content analysis, and synthesizing data on digital well-being interventions, consumer behavior, and transformative marketing strategies. Findings: The research findings reveal the existence of a “Technology and Consumer Well-being Paradox Model,” in which connectivity acts as a double-edged sword: it facilitates autonomy and personal growth while simultaneously triggering technostress and cognitive load. It was found that the current market is dominated by strategies of “individual responsabilization” through digital self-control tools; however, there are strategic opportunities for brands to integrate digital well-being into their value propositions to enhance trust and meaningful engagement, particularly through “eudaimonic entertainment” and corporate digital responsibility. Implications & Recommendations: Organizations are advised to adopt empathetic digital designs that prioritize the quality of interactions over the quantity of attention. Recommendations include aligning communication strategies with “right to disconnect” regulations and leveraging AI for personalization that supports users’ mental health. Contribution & Value Added: This study makes a theoretical contribution by conceptualizing digital well-being as a strategic asset within the Transformative Consumer Research (TCR) framework, offering a new perspective that holistically aligns business profitability with human well-being.